2015
DOI: 10.1177/1933719115572483
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age and Contractility of Human Myometrium in Pregnancy

Abstract: There is controversy as to whether maternal age exerts an influence on the contractility of human myometrium in pregnancy. The aim of this study was to examine a series of functional contractile parameters of human myometrium in vitro, over a broad range of maternal ages. Myometrial tissue specimens were obtained at cesarean delivery from 32 women with maternal ages ranging from 28 to 52 years. Using in vitro recordings, a number of contractile parameters including maximal amplitude, mean contractile force, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
(35 reference statements)
2
16
0
1
Order By: Relevance
“…Previous studies from our group have examined a wide range of contractile parameters in relation to maternal age, and no significant difference was found. 13 We are of the view that this difference is unlikely to have had an influence on the results obtained.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous studies from our group have examined a wide range of contractile parameters in relation to maternal age, and no significant difference was found. 13 We are of the view that this difference is unlikely to have had an influence on the results obtained.…”
Section: Discussionmentioning
confidence: 90%
“…The results from some of the biopsy samples included in this study have previously been reported in different contexts. [11][12][13] Strips of myometrium were excised from the upper lip of the incision in the lower uterine segment as described previously. 11,[13][14][15] The myometrial strips were then placed in physiological salt solution (PSS) at 4°C.…”
Section: Tissue Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as this and others studies have shown, the association appears to be independent of medical or perinatal complications. Furthermore, despite biologic factors, such as the inefficiency of the ageing myometrium, having been suggested as an explanation, recent evidence in this area does not indicate this to be the case . In addition, Zaki et al, in an analysis of the US Consortiom on Safe Labor data (N = 120,442), found that the progress of first‐stage labor was shorter in older women, regardless of parity, but that the second stage was longer in older, nulliparous women .…”
Section: Discussionmentioning
confidence: 99%